2016
DOI: 10.1021/acsami.5b09987
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Size Effect Observed in ZnO-Au Composite Photocatalysts

Abstract: Semiconductor-metal nanocomposites prepared with well-defined gold nanoclusters, such as Au25, Au144, and Au807, showed size-dependent photocatalytic activities for the reduction of nile blue and azobenzene. Whereas the photoreduction of nile blue was directly related with the charge separation and transfer rate from the photoexcited ZnO to gold nanoclusters, the photoreaction of azobenzene showed unexpected size effect with a clear threshold. Mechanistic investigations revealed that the photoreduction of azob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 30 publications
(69 reference statements)
1
34
0
Order By: Relevance
“…As the irradiation time increased, the fluorescence of Rh101 decreased (inset of Figure (a)), suggesting a decrease in the concentration of Rh101 because of the photoreaction. On the other hand, the photoluminescence intensity of ZnO remained unchanged, as was expected for a stable catalyst. Consequently, the time evolution of spectra indicated photocatalytic activity of ZnO in the degradation of Rh101 (Figure (b)), which implied a single‐electron reduction process of Rh101 by electrons supplied from the conduction band of ZnO …”
supporting
confidence: 64%
See 2 more Smart Citations
“…As the irradiation time increased, the fluorescence of Rh101 decreased (inset of Figure (a)), suggesting a decrease in the concentration of Rh101 because of the photoreaction. On the other hand, the photoluminescence intensity of ZnO remained unchanged, as was expected for a stable catalyst. Consequently, the time evolution of spectra indicated photocatalytic activity of ZnO in the degradation of Rh101 (Figure (b)), which implied a single‐electron reduction process of Rh101 by electrons supplied from the conduction band of ZnO …”
supporting
confidence: 64%
“…The details of the preparation and measurement system have been reported elsewhere . Zinc oxide nanoparticles, rhodamine 101, aniline, and methanol were purchased from Sigma‐Aldrich (St. Louis, MO, USA).…”
Section: Experimental Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For another thing, significant efforts have been devoted to enhancing the photocatalytic performance and suppressing the photocorrosion by surface modification, such as combination with another semiconductor, deposition of noble metals, and coupling with versatile carbon materials [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Formore than two decades, investigations were performed in the absence of precise structural information. It was reported that thiolate-protected Au 144 clusters show promising catalytic activities [24][25][26][27][28] and electrochemiluminescence, [29,30] and can be employed as precursors in the synthesis of Au 99 [31] and Au 133 [12,13,32] nanoclusters.M oreover,A u 144 has applications in organic solar cell [33] and floating memory devices, [34] etc.More importantly, it was also found that thiolate-protected Au 144 exhibits both molecular and bulklike behaviors,w ith its size in the critical transition range.F or example,A u 144 (SR) 60 exhibits ah ighly structured UV-vis-NIR spectrum with absorption bands over the entire region. [35,36] This spectrum indicates the molecular nature of Au 144 ,and was also supported by density functional theory (DFT) calculations.…”
mentioning
confidence: 99%